Developing a Social Enterprise Performance Scale and Examining the Relationship Between Entrepreneurs’ Personality Traits and Their Perceived Enterprise Performance - Chao-Tung Liang; Li-Pei Peng; Shu-Nung Yao; Chaoyun Liang (Journal of Entrepreneurship, Management and Innovation)

(untitled)
On the basis of the lack of measurement tools and the research gap regarding social entrepreneurship, three studies were conducted to develop a new measure of social enterprise (SE) performance that is empirically valid and easy to administer. The purpose of this measure was to examine the relationship between entrepreneurs’ personality traits and their perceived SE performance. The results indicated that SE performance can be assessed using four dimensions: personal issues, social aspects, business elements, and service programmes. Extraversion positively influenced service programmes, and openness negatively affected service programmes. Neuroticism and conscientiousness positively predicted personal issues and service programmes, and agreeableness positively predicted all dimensions of perceived SE performance. The results also demonstrated the curvilinear relationship of the U-shaped curve between neuroticism and personal issues and the social aspects of SE performance. Furthermore, the results showed the curvilinear relationship of the inverted U-shaped curve between agreeableness and the four dimensions of SE performance.